Demonstration Methodology in Tafsir Movement/Haraki from the Perspective of Shalah Abdul Fatah al-Khalidi - Sofiyul Mubarok, Achmad; Salman Alfarisi (Universitas Ahmad Dahlan, 2024)
This paper explores the history and methodology of demonstrations from the classical to the contemporary era. To this day, the phenomenon of demonstrations cannot be eradicated in the world. Initiated by the West, demonstrations are worth the spirit of fighting against the government if the policy is not pro-people which ends with anarchist actions. While in Islam, demonstrations are conceptualized with two terms, Muzhaharaah and Masirah. What is allowed in Islam is Masirah, because it contains good procedures and is not anarchic. Although demonstrations in the Qur'an are not mentioned with certainty, but as a secondary text or interpretation of the Qur'an explains the demonstration as a whole which is packaged in the tafsir movement/haraki. This study aims to examine demonstrations in Islam with the paradigm tafsir movement/haraki. This research is qualitative in nature by using the method of tafsir movement/haraki. The results of this study indicate that demonstrations in Masirah-based Islam can maintain Islamic values intact. And by applying the methodology of tafsir haraki Shalah Abdul Fatah Al-Khalidi, demonstrations contain the value of movement, da'wah, and education that does not injure social and religious norms.